INDAPAMIDE EFFECTS ON FREE OXYGEN RADICALS PRODUCED BY BLOOD PHAGOCYTES IN PATIENTS WITH HEART FAILURE - E. I. Astashkin; M. G. Glezer; E. A. Petrov; I. N. Sokolov (Российский кардиологический журнал, 2012)
Aim. To study the effects of a thiazide-like diuretic indapamide (Ind) on the levels of free oxygen radicals generated by blood phagocytes and isolated neutrophils in patients with heart failure (HF). Material and methods. Using whole blood samples and isolated neutrophils of 16 HF patients (NYHA Functional Class II–III), the generation of free oxygen radicals was examined with a chemiluminometre “Biotox-7”, in the presence of luminophores – lucigenin (30 mkM) and luminol (50 mkM). The standard stimulators of blood phagocytes and neutrophils were bacterial tripeptide (FMLP, 3 mkM) and phorbol ester (PMA, 1 mkM). The generation of superoxide anions (O2-) and hydroxyl radicals was continuously assessed by the number of impulses per second and presented as integral chemiluminescence (summary value for 10 minutes). Inhibiting effects of varied Ind concentrations were assessed by the decrease (%) in the peak stimulated luminescence. Antioxidant activity of Ind was studied in the cell-free medium generating hydroxyl radicals. Statistical analysis of the data was performed with the use of SigmaPlot software. Results. At baseline, the blood of HF patients contained pre-activated (primed) phagocytes, as shown by the “spontaneous” production of superoxide anions due to neutrophil adhesion on cuvette walls. PMA markedly increased the production of oxygen radicals. In the neutrophil suspension, Ind dose-dependently (0,5–2 mkM) reduced the peak PMA response levels of superoxide anions up to the baseline levels. Moreover, Ind demonstrated a similar effect in whole blood samples of HF patients. FMLP increased the production of oxygen radicals and potentiated the subsequent response of phagocytes to PMA. Ind (2 mkM), when added after FMLP and PMA, reduced the post-stimulation levels of superoxide anions up to baseline values. The initial exposure of blood samples to Ind decreased spontaneous generation of oxygen radicals and the magnitude of subsequent response to FMLP and PMA. Antioxidant effects of Ind were also observed in the cell-free medium, which suggests a direct interaction between Ind and oxygen radicals. Conclusion. Low Ind concentrations provided a marked antioxidant effect, which could be clinically significant in the management of HF patients.